Preceptorship terhadap Kepatuhan Melaksanakan SPO Pemasangan Infus dan Pendokumentasian dalam Melakukan Tindakan Pemasangan Infus - Marlina, Meli (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of preceptorship on compliance in implementing SOP for infusion installation and documentation in carrying out infusion installation actions. The method used is a quasi-experiment with a one-group pretest–post-test design. The results showed compliance in infusion installation by the SOP before and after preceptorship increased from 67.6% to 88.2%. At the same time, compliance in documentation in carrying out actions before and after preceptorship rose from 52.9% to 85.3%. In conclusion, preceptorship affects compliance in implementing SOP for infusion installation and documentation in carrying out infusion installation actions in the Inpatient Room of Bertha Medika Hospital, Sukabumi Regency. Keywords: Compliance, Documentation, Infusion Installation, Preceptorship